2008
DOI: 10.1017/s0007114508027438
|View full text |Cite
|
Sign up to set email alerts
|

A novel method to remotely measure food intake of free-living individuals in real time: the remote food photography method

Abstract: The aim of the present study was to report the first reliability and validity tests of the remote food photography method (RFPM), which consists of camera-enabled cell phones with data transfer capability. Participants take and transmit photographs of food selection and plate waste to researchers/clinicians for analysis. Following two pilot studies, adult participants (n 52; BMI 20 -35 kg/m 2 inclusive) were randomly assigned to the dine-in or take-out group. Energy intake (EI) was measured for 3 d. The dine-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
260
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 268 publications
(283 citation statements)
references
References 29 publications
11
260
0
4
Order By: Relevance
“…One prominent approach is 24-hour recall, in which a trained dietitian interviews a subject about her consumption over the previous day [16]. Accuracy depends on the subject's memory and honesty, and the technique requires a costly expert to conduct analysis.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…One prominent approach is 24-hour recall, in which a trained dietitian interviews a subject about her consumption over the previous day [16]. Accuracy depends on the subject's memory and honesty, and the technique requires a costly expert to conduct analysis.…”
Section: Related Workmentioning
confidence: 99%
“…Our work is inspired by the Remote Food Photography Method (RFPM) [16], a novel approach from the nutrition literature. Rather than remembering foods or writing down records, users take two photographs of each meal: one at the beginning of the meal and one at the end documenting the leftovers.…”
Section: Introductionmentioning
confidence: 99%
“…Alcohol use is prevalent among young adults; most (78%) of US adults aged [18][19][20][21][22][23][24] report drinking alcohol in the past year [1]. Alcohol is calorically dense [2] and heavy episodic drinking during young adulthood can increase the risk of excess weight gain and the transition to obesity [3].…”
Section: Introductionmentioning
confidence: 99%
“…SmartIntake® is used to capture images of food selection and plate/drink waste in near real-time in people's natural environment. SmartIntake ® photos are analyzed by nutrition experts to estimate energy and nutrient content using standardized methods [19,20], eliminating the need for participants to accurately recall and report portion sizes. The RFPM and SmartIntake ® have excellent evidence for validity in measuring energy intake in the general adult population; SmartIntake ® estimates had only a 3.7% error rate when compared to energy expenditure estimates from doubly-labeled water in weight-stable adults [17].…”
Section: Introductionmentioning
confidence: 99%
“…48 For example, recent research has identified the value in using cell phone cameras to document food choices and quantities. 49 Many mobile systems provide assessment that is closer in time and proximity to the actual barriers to self-management but still rely on self-report. However, any automation or mobile monitoring of health behaviors will make the integration of adherence data into clinical management much more feasible.…”
mentioning
confidence: 99%